2009
DOI: 10.4049/jimmunol.0802197
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin- and Dynamin-Dependent Endocytic Pathway Regulates Muramyl Dipeptide Internalization and NOD2 Activation

Abstract: Muramyl dipeptide (MDP), the NOD2 agonist, induces NF-κB and MAPK activation leading to the production of antimicrobial and proinflammatory molecules. MDP is internalized into acidified vesicles in macrophages. However, the endocytic mechanism of MDP uptake that induces NOD2 signaling is unknown. We now report the identification of an endocytosis pathway dependent on clathrin and dynamin that mediates MDP internalization and NOD2 activation. Intracellular MDP uptake was inhibited by chlorpromazine, a drug that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
91
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 46 publications
8
91
1
1
Order By: Relevance
“…A recent report has demonstrated that MDP was internalized by macrophages through clathrin-dependent endocytosis (39), which supports our findings in HEK293T cells. However, MDP entry in macrophages appeared to require V-ATPase-dependent endosomal acidification, contrasting with our observations in HEK293T cells.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A recent report has demonstrated that MDP was internalized by macrophages through clathrin-dependent endocytosis (39), which supports our findings in HEK293T cells. However, MDP entry in macrophages appeared to require V-ATPase-dependent endosomal acidification, contrasting with our observations in HEK293T cells.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, a number of muramyl peptide transporters could exist and be differentially expressed in specific cell types and/or subcellular compartments. This hypothesis is supported by the fact that SLC15A1 was identified as an MDP transporter in Caco-2/bbe epithelial cells (40), but found to be dispensable for mediating MDP entry in macrophages (39). Similarly, SLC15A2 has been shown to trigger transport of the Nod1 ligand iE-DAP in human upper airway epithelial cells (41), but was found to be dispensable in our assays.…”
Section: Discussionsupporting
confidence: 70%
“…To reveal the primary physiological pathway of incorporation, two representative CPPs, colon cancer-homing CPP2 and myeloid leukaemia-homing CPP44, were chosen as examples. First, their internalization was examined using 5-(N-ethyl-N-isopropyl) amiloride (EIPA) 10 , Dynamin inhibitor I (DI; Dynasore) 11 , and chlorpromazine (CPZ) 12 . Pretreatment of the cells with EIPA, a macropinocytosis inhibitor, prevented the entry of polyarginine (r9) 13 in a dose-dependent manner; however, the entry of CPP44 into primary AML cells was not impeded.…”
Section: Isolation Of Tumour Lineage-homing Cppsmentioning
confidence: 99%
“…3B). Finally, extracellular MDP can get access to the host cytosol through the intestinal apical di-/tripeptide transporter, hPepT1 [21] or by a clathrin-and dynamin-dependent endocytic pathway [22,23] (Fig. 3C).…”
Section: Nod2-dependent Nf-kb and Mapks Activation Pathways In Responmentioning
confidence: 99%